The Evaluation of Output Convergence in Several Central and Eastern European Ccountries - Lyubenko, Andriy (Ekonomika, 2015)
The Ukrainian integration into the world economic community means the unification of NATIONAL standards, the financial reporting, auditing and state financial control, its closest approach to the international requirements. It is difficult to overestimate the value of standardization for the economic environment and state administration. The advantages of standardization consist not only in the simplification of processes and procedures, but also in their strengthening due to reliability, which is based on the identity of understanding the rules and norms, and the high quality based on the approach regarding the questions of responsibility and introducing penalties for the possible violations. The author analyzes the development of the state financial control in Ukraine according to the INTOSAI standards. The article presents the necessity to develop and implement the national standards of financial control in accordance with the INTOSAI standards.